2021
DOI: 10.3390/cancers13205060
|View full text |Cite
|
Sign up to set email alerts
|

Current Technologies for RNA-Directed Liquid Diagnostics

Abstract: There is unequivocal acceptance of the variety of enormous potential liquid nucleic acid-based diagnostics seems to offer. However, the existing controversies and the increased awareness of RNA-based techniques in society during the current global COVID-19 pandemic have made the readiness of liquid nucleic acid-based diagnostics for routine use a matter of concern. In this regard—and in the context of oncology—our review presented and discussed the status quo of RNA-based liquid diagnostics. We summarized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…The pool of informative markers (Table 1, section A and B) was investigated individually in the literature to identify significant changes in expression linked to other Fig. 2 PRISMA schema [26] for the systematic review of literature 3. A total of 90 relevant studies were identified reporting significant expression changes in these specific miRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pool of informative markers (Table 1, section A and B) was investigated individually in the literature to identify significant changes in expression linked to other Fig. 2 PRISMA schema [26] for the systematic review of literature 3. A total of 90 relevant studies were identified reporting significant expression changes in these specific miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several types of blood cells including erythrocytes, platelets, leukocytes and megakaryocytes can also release miRNAs [ 22 , 23 ] which makes the analysis of blood samples problematic unless prepared carefully [ 24 ]. As dysregulation of miRNAs has already been associated with many severe diseases [ 25 ], these extracellular miRNAs are of great interest as biomarkers due to their properties of being potentially disease-specific, stable, quantifiable and easily extracted from a range of clinical samples [ 26 ]. In this manuscript we review the potential of microRNAs (miRNAs) as biomarkers for chemotherapy-induced cardiotoxicity in BC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue biopsy as a morphology‐based detection method is still the gold standard for the diagnosis of solid tumors. However, growing evidence suggests that comprehensive molecular profiling can also be used to help monitor and guide treatment for cancer [252–254]. In fact, tissue biopsy does not always accurately reflect the heterogeneity of the cancer, nor is it always readily available for cancer screening or evaluating response to treatment due to invasiveness, inaccessibility, and related complications [251, 255–257].…”
Section: Applications Of Plasma Proteomics/peptidomics In Covid‐19 An...mentioning
confidence: 99%
“…The presence of DNA and RNA from non-malignant cells in ctDNA and cfRNA sample can decrease diagnostic sensitivity and increase false negative rates, while the presence of DNA and RNA from non-malignant cells that carry cancer-associated mutations can decrease assay specificity and increase false positive rates. Both LB ctDNA and cfRNA are susceptible to degradation by circulating nucleases in the interval between LB collection and its processing for analysis or cryopreservation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%